DIALECTIC MOTIVATION, BEHAVIOR AND SPIRITUAL PEAK EXPERIENCE IN THE PERSPECTIVE OF ISLAMIC PSYCHOLOGY - Athoillah Islamy (IAIN Batusangkar, 2019)
This study aims to find the correlation of motivation, behavior and spiritual peak experience in the view of Islamic psychology. This type of research, namely qualitative research in the form of literature study. The primary data source of this research, namely the theory of hierarchy of human basic needs from Abraham Maslow. Meanwhile, secondary research data sources, namely various other relevant western motivational theories. The theory is used as a knife of analysis, namely the theory of motivation of the human soul from al-Ghazali which includes dimensions of heart, reason and lust. This study concludes that in the perspective of Islamic psychology there is a strong relationship between motivation and the behavior of every human being in the process of achieving spiritual peak experiences. The relationship of motivation and human behavior in the perspective of Islamic psychology that is more likely to emphasize religious motives (spiritual), both in psychological and physiological conditions of humans. motivation and behavior in Islam are very closely related to various stages in the process towards the ultimate spiritual human experience.